Narrations of Amro bi Murra Al-Juhani in the nine books: An Analytic Study - Dawood , Taha (Islamic Sciences Journal, 2023)
This research was specialized in studying the hadiths of the companion Amr ibn Murrah in the nine books, an analytical study to clarify the meanings and benefits they contain. The rhetoric, the strange, the explanation, the overall meaning, and the benefits it contains. The number of hadiths reached three, distributed on topics: the justice of the imam in the parish, genealogy, and the pillars of faith, and the results of their study were many benefits, the most important of which are: that the imam who hides from his flock, God will be veiled from him on the Day of Resurrection, and that genealogy knowledge is necessary. The division of inheritances, knowledge of efficacy, blood money, and the great leadership, and steadfastness in matters of faith, and death over them is a reason for attaining the rank of prophets and truthful ones on the Day of Resurrection. The importance of the research comes from the fact that it has shed light on one of the relatively unknown personalities of the Companions, and introduced us to his efforts and stances in the service of Islam, as we introduced him to his relatively few hadiths, and indicated their degree, benefits, and provisions.